Peningkatan Sertifikat Halal UMKM Kecamatan Cileunyi oleh Lembaga Pemeriksa Halal UIN Sunan Gunung Djati Bandung Menurut Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal Perspektif Siyasah Dusturiyah - Nurul Fuadha Siregar; Chaerul Shaleh; Taufiq Alamsyah (Jurnal Hukum Lex Generalis, 2025)
The enhancement of halal product assurance for Micro, Small, and Medium Enterprises (MSMEs) has become one of the strategic national agendas in realizing consumer protection for Muslims, as stipulated in Law Number 33 of 2014 concerning Halal Product Assurance. This study aims to analyze the role of the Halal Inspection Agency (LPH) of UIN Sunan Gunung Djati Bandung in facilitating halal certification for MSMEs in Cileunyi Subdistrict, as well as to examine its implementation from the perspective of Siyasah Dusturiyah. This research employs a juridical-empirical approach using a descriptive-analytical method, supported by primary data obtained through observation and interviews, and secondary data from literature studies and official documents. The results of the study show that the LPH plays an active role in providing education, technical assistance, and conducting halal audits, which have a positive impact on increasing the number of certified MSMEs, enhancing the sharia awareness of business actors, and improving product competitiveness. The challenges encountered include low halal literacy and a limited number of auditors. From the Siyasah Dusturiyah perspective, the implementation of halal inspections reflects the state's role in ensuring public welfare through synergy between religious institutions, the government, and society. This activity also serves as a concrete form of integration of the functions of Islamic higher education in socio-economic development based on sharia values.